High Performance and Cost‐Effective Direct Methanol Fuel Cells: Fe‐N‐C Methanol‐Tolerant Oxygen Reduction Reaction Catalysts. Issue 15 (4th July 2016) - Sebastián, David; Serov, Alexey; Artyushkova, Kateryna; Gordon, Jonathan; Atanassov, Plamen; Aricò, Antonino S.; Baglio, Vincenzo
Abstract: Direct methanol fuel cells (DMFCs) offer great advantages for the supply of power with high efficiency and large energy density. The search for a cost‐effective, active, stable and methanol‐tolerant catalyst for the oxygen reduction reaction (ORR) is still a great challenge. In this work, platinum group metal‐free (PGM‐free) catalysts based on Fe‐N‐C are investigated in acidic medium. Post‐treatment of the catalyst improves the ORR activity compared with previously published PGM‐free formulations and shows an excellent tolerance to the presence of methanol. The feasibility for application in DMFC under a wide range of operating conditions is demonstrated, with a maximum power density of approximately 50 mW cm −2 and a negligible methanol crossover effect on the performance. A review of the most recent PGM‐free cathode formulations for DMFC indicates that this formulation leads to the highest performance at a low membrane–electrode assembly (MEA) cost. Moreover, a 100 h durability test in DMFC shows suitable applicability, with a similar performance–time behavior compared to common MEAs based on Pt cathodes. Abstract : No nobles here ! Platinum group metal‐free materials based on Fe‐N‐C are investigated as cost‐effective, active, stable and methanol‐tolerant catalysts for the oxygen reduction reaction (ORR) in direct methanol fuel cells (DMFCs). Outstanding performance of DMFCs is observed, even at high methanol concentration (10 m ), owing to improved ORR activity and high tolerance to the alcohol.